COVID-19 pandemic in the State of Paraná: a spatio-temporal analysis of health indicators (Acta Scientiarum. Health Sciences, 2023)
Monitoring COVID-19 health indicators allows the organization and implementation of policies to contain the disease. In this regard, the present study aimed to analyze the evolution of these indicators in the State of Paraná. This was a cross-sectional study, analyzing secondary quantitative data from the 22 Health Regions, of epidemiological bulletins from the Health Department of the state of Paraná, between March 2020 and March 2022. The variables Incidence Rate, Mortality Coefficient, and Lethality Coefficient were analyzed using descriptive statistics and presented through tables and thematic maps. The results showed that most of the Health Regions have high Mortality Coefficient and Incidence Rate after two years, especially the ninth Region (based in Foz do Iguaçu), which maintained a high incidence throughout the analyzed period. Lethality, on the other hand, showed a significant decrease within the Health Regions at the end of the period, demonstrating a decrease in the severity of the disease, which can be explained by the influence of the Vaccination Plan on this indicator. In addition, the first (based in Paranaguá) and second (based in Curitiba) health regions showed high indicators of Mortality and Lethality over time. The study highlighted the importance of monitoring health indicators to organize public policies to contain the disease in the State, especially the Vaccination Plan against COVID-19.